The Role of Self-Awareness in Mediating the Influence of Islamic Boarding School Policies and Regulations on the Competency Development of Santri: PLS-SEM Approach - Purnomo, Ahmad Kosim; Munir, Moh.; Daryono, Rihab Wit (AL-ISHLAH: Jurnal Pendidikan, 2024)
Self-awareness allows individuals to be more aware of how they respond to lodge policies and regulations. They will be better able to be aware of these policies and regulations in influencing their behavior, attitudes, thought patterns, and competency development. This research explores the role of self-awareness in mediating the influence of Islamic boarding school policies and regulations and competency development. Quantitative methods with PLS-SEM analysis were used to test the feasibility of discriminant validity and research hypotheses. Data was collected through a questionnaire with 50 students at the Al-Idris Islamic Boarding School, Banyudono, Ponorogo using the purposive sampling method. The results of the analysis show that Islamic boarding school policies have a significant positive effect on self-awareness (β=0.521; ρ=0.000) and competency development (β=0.295; ρ=0.014). Furthermore, self-awareness was proven not to mediate the influence of policies (β=0.125; ρ=0.103) and Islamic boarding school regulations (β=0.075; ρ=0.129) on the competency development of students. The research results show that student self-awareness is strongly influenced by Islamic boarding school policies and regulations, which in turn support the development of student Competency. The implications of this study show the importance of education that focuses on developing students' self-awareness as part of efforts to prepare them to participate actively in society. The suggestion from this study is that Islamic boarding school education should focus more on developing self-awareness as a strategic step in developing their competency.